Preserflo-MicroShunt: Postoperative Effects on Endothelial Cell Density and Corneal Thickness - Sebastian Dierse; Eliane Luisa Esser; Ralph-Laurent Merté; Sami Al-Nawaiseh; Martin Dominik Leclaire; Nicole Eter; Viktoria Constanze Brücher (Biomedicines, 2025)
Background: The aim of this study was to evaluate the effects of Preserflo implantation on endothelial cell density (ECD), corneal thickness, intraocular pressure (IOP), and the use of antiglaucoma medications over a 12-month follow-up period. Methods: A total of 53 eyes from 53 patients undergoing Preserflo implantation were included in this prospective study. ECD, corneal thickness, IOP, and the number of antiglaucoma medications were measured at baseline, 3 months, and 12 months postoperatively. Statistical analysis was performed using paired t-tests and Wilcoxon signed-rank tests for non-normally distributed data. Results: There was no significant reduction in ECD at 3 months (p = 0.695) or 12 months (p = 0.229) compared to baseline. However, a significant reduction in corneal thickness was observed at 3 months (p = 0.008), with no significant change at 12 months (p = 0.118). A significant reduction in IOP was noted at both 3 months (from a preoperative median of 23.5 mmHg to 11.5 mmHg, p < 0.001) and 12 months (from 23.5 mmHg to 13.0 mmHg, p < 0.001). Additionally, there was a significant decrease in the use of antiglaucoma medications, from a preoperative median of 3.0 medication classes to 0.0 classes at both 3 months (p < 0.001) and 12 months (p < 0.001). Conclusions: Preserflo implantation resulted in a significant reduction in IOP and the need for antiglaucoma medications, with no significant impact on endothelial cell density and corneal thickness after 12 months. These findings suggest that Preserflo implantation is an effective procedure for IOP control and medication reduction, with favorable outcome for corneal health after one year.